Mixed Layer Problem of a Three-Dimensional Drift-Diffusion Model for Semiconductors (Journal of Partial Differential Equations, 2017)
" The quasineutral limit and the mixed layer problem of a three-dimensional drift-diffusion model is discussed in this paper. For the Neumann boundaries and the general initial data, the quasineutral limit is proven rigorously with the help of the weighted energy method, the matched asymptotic expansion method of singular perturbation problem and the entropy production inequality."
Keywords: Drift-diffusion model; quasineutral limit; mixed layer